Quantitative and qualitative research: exploring the advantages of different research methodologies - Ugalde Binda, Nadia (2013)
The research process has as a result the creation of knowledge through solving a research problem. thus, research methodology refers to all the decisions that the researcher makes to achieve their research goals and deals with issues such as research design, the strategy to use, the study sample, the methods used to collect the information, techniques to be used in the analysis of information and the criteria to be used to increase the quality of work, among others. the current research designs revolve around two major paradigms:quantitative model and the qualitative model. this article reviews both perspectives and explains when and why it is appropriate to use each one.